Habitat heterogeneity and pollinators: Bees in fragmented landscapes (Hymenoptera : Apidae) - Patricio, Gleiciani Buerger [UNESP]; Gomig, Elizandra Goldoni [UNESP] (California State University, 2008)
This text presents the main studies that report the effect of habitat degradation upon plant-pollinator interactions and the importance of the presence of native vegetation remnants to pollinators, which leads to the need for conservation measures.
Keywords: habitat fragmentations; plant-pollinator interaction; bees; conservation